The Road to Gandolfo - Ludlum, Robert (Bantam Books, 1992)
War hero and infamous ladies? man General MacKenzie Hawkins is a living legend. His life story has even been sold to Hollywood. But now he stands accused of defacing a historic monument in China?s Forbidden City. Under house arrest in Peking with a case against him pending in Washington, this looks like the end of Mac?s illustrious career. But he has a plan of his own: kidnap the Pope. What?s the ransom? Just one American dollar? -- Praise for Robert Ludlum? "Don?t ever begin a (Robert) Ludlum novel if you have to go to work the next day."?Chicago Sun-Times? "Ludlum stuffs more surprises into his novels than any other six-pack of thriller writers combined."?